Engineering education for sustainable development (EESD) for undergraduate engineering programmes in Malaysia: a stakeholder defined framework - Sivapalan, Subarna. (2015)
The Institution of Engineers Malaysia (IEM) and the Board of Engineers Malaysia (BEM) stress the need for Malaysian engineering graduates to be able to integrate sustainable development knowledge, skills and values in their professional practice. The 2012 Engineering Accreditation Council (EAC) manual outlines 12 outcomes that students of Malaysian institutions of higher learning offering engineering programmes are expected to develop upon completion of their studies. Of the 12 outcomes, three are explicitly linked to sustainable development. While institutions of higher learning are required to develop the prescribed skill set using outcome based approaches to learning, integration measures are not specifically stipulated. 30 hypothetical competences were developed as a means of addressing the issue of integrating sustainable development outcomes within the undergraduate engineering programme curriculum. Using a private higher learning institution offering engineering programmes as a case study, this study set out to explore the views of the institution’s stakeholders, i.e. the final year undergraduate engineering students, academicians, university management and engineers, as well as education for sustainable development experts and ESD practitioners on (a) the extent to which sustainable development and education for sustainable development is incorporated within the engineering curriculum of the higher learning institution (b) the inclusion of sustainable development programme and module learning outcomes within the undergraduate engineering curriculum and how it can be included within the curriculum, and (c) the additional components needed for the EESD framework for undergraduate engineering education in Malaysia. Respondents’ perspectives were sought through a triangulation mixed methods approach, through surveys, interviews and analysis of documents. Findings of the study were then used to develop the proposed (a) guidelines to incorporate sustainable development competences holistically within undergraduate engineering programme outcomes and common module learning outcomes, and the (b) Whole Institution EESD Framework.